The Poverty of Population and its Impact on Formation of Food Security - Pchelianska Halyna O. (Bìznes Inform, 2017)
The article is aimed at studying the causes of poverty, its negative manifestations, identifying the impact of poverty, determining its impact on food security, and finding ways to overcome it. It has been determined that the structural causes of poverty are considered to be the general macroeconomic and political living conditions of population. The individual approach implies that human poverty is influenced by both the subjective (family, education, skills, job availability or absence) and the institutional factors. The author characterizes the economic, social, and political consequences of poverty, their impact on food security. The impact of structural factors on the level of poverty in Ukraine was analyzed. The article explores the level of poverty in different categories of households, i.e.: households in rural and urban areas, with and without children. It has been proven that the level of poverty affects the formation of household food security. The main directions for overcoming poverty and improving food security have been proposed.